2021
DOI: 10.3390/s21103414
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Exact Valence and Arousal Values from EEG

Abstract: Recognition of emotions from physiological signals, and in particular from electroencephalography (EEG), is a field within affective computing gaining increasing relevance. Although researchers have used these signals to recognize emotions, most of them only identify a limited set of emotional states (e.g., happiness, sadness, anger, etc.) and have not attempted to predict exact values for valence and arousal, which would provide a wider range of emotional states. This paper describes our proposed model for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…Another way is to use the existing, well-known database in the field of emotion recognition based on EEG, including DEAP ( Izquierdo-Reyes et al, 2018 ), MAHNOB-HCI ( Izquierdo-Reyes et al, 2018 ), GAMEEMO ( Özerdem and Polat, 2017 ), SEED ( Lu et al, 2020 ), LUMED ( Cimtay and Ekmekcioglu, 2020 ), AMIGOS ( Galvão et al, 2021 ), and DREAMER ( Galvão et al, 2021 ). After obtaining the original EEG signal related to emotion states, the following operation is to preprocess the EEG signal to improve the quality of the EEG data.…”
Section: Acquisition Of Electroencephalography Signals For Emotion Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way is to use the existing, well-known database in the field of emotion recognition based on EEG, including DEAP ( Izquierdo-Reyes et al, 2018 ), MAHNOB-HCI ( Izquierdo-Reyes et al, 2018 ), GAMEEMO ( Özerdem and Polat, 2017 ), SEED ( Lu et al, 2020 ), LUMED ( Cimtay and Ekmekcioglu, 2020 ), AMIGOS ( Galvão et al, 2021 ), and DREAMER ( Galvão et al, 2021 ). After obtaining the original EEG signal related to emotion states, the following operation is to preprocess the EEG signal to improve the quality of the EEG data.…”
Section: Acquisition Of Electroencephalography Signals For Emotion Recognitionmentioning
confidence: 99%
“…Unlike researches listed in Table 1 , which only identified a limited set of emotional states (e.g., happiness, sadness, anger, etc. ), Galvão et al (2021) were dedicated to predicting the exact values of valence and arousal in a subject-independent scenario. The systematic analysis revealed that the best prediction model was a KNN regressor ( K = 1) with Manhattan distance, features from the alpha, beta, gamma bands, and the differential asymmetry from the alpha band.…”
Section: Classification Of Emotion-related Electroencephalography Signalsmentioning
confidence: 99%
“…Poor-quality sleep negatively affects work performance [ 1 ] as well as emotional states [ 2 , 3 ]. A common measure of poor-quality sleep is sleep arousals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different models or theories have been developed and used by psychologists or cognitive neuroscientists to distinguish between emotions based on facial expressions. The categorization of human emotions is mainly based on two perspectives: discrete and dimensional [ 11 ]. In the dimensional perspective, emotions are represented by the valence and arousal dimensions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the dimensional perspective, emotions are represented by the valence and arousal dimensions [ 12 ]. The valence dimension indicates the intrinsic attractiveness or aversion of an event, object, or situation, and it varies from negative to positive [ 11 ]. Arousal, on the other hand, indicates whether the subject is responsive at that given moment and for that given stimulus, as well as how active he/she is.…”
Section: Introductionmentioning
confidence: 99%